Effect of immersion and thermocycling in different beverages on the surface roughness of single- and multi-shade resin composites - Aiah A. El-Rashidy; Omar Shaalan; Rasha M. Abdelraouf; Nour A. Habib (BMC, 2023)
Abstract Background Resin composite restorations are highly esthetic restorations, which should have and maintain high surface polish. However, esthetic restorations are subjected to different beverages at variable temperatures, which may affect their surface roughness. This study aimed to evaluate the surface roughness of single-shade (Omnichroma) and multi-shade (Filtek Z350XT) composite materials, following aging by immersion and thermocycling in different beverages, simulating one year of clinical service. Methods Thirty specimens of each material were prepared and divided into 6 subgroups (n = 5). In each material, the grouping of the specimens was as follows: the first subgroup was the as-prepared specimens stored dry without immersion or thermocycling. The second, third, and fourth subgroups were immersed in saliva, tea, and red wine, respectively, for 12 days at 37 °C. The fifth and sixth subgroups were thermocycled for 10,000 cycles, in tea (the fifth between 37 and 57 °C) and in red wine (the sixth between 37 °C and12°C). The resultant surface roughness was measured by two different methods, stylus profilometer and atomic force microscopy (AFM). Intergroup comparison was performed using independent t test, while intragroup comparison was performed using one-way analysis of variance (ANOVA) followed by Tukey's post-hoc test. Results Intergroup comparison between both composites showed no statistically significant differences in all groups using the stylus profilometer roughness measurements (P>0.05), while the AFM measurements showed significant difference (P ≤ 0.05) within all storage media except the as-prepared control (P = 0.0645), where nanofilled Filtek Z350 XT showed lower nano-roughness. Intragroup comparison data were variable, depending on the material, aging conditions, and roughness assessment tool. However, the resultant average surface roughness (Ra) values in all groups did not exceed the threshold value of Ra 0.2 μm. Conclusions Both resin composites attained and retained a clinically acceptable surface finish after immersion and thermocycling in different beverages.